2020
DOI: 10.3755/galaxea.22.1_27
|View full text |Cite
|
Sign up to set email alerts
|

Genus-specific bleaching at Con Dao Islands, Southern Vietnam, June 2019

Abstract: Coral communities in the shallow waters of Con Dao islands, located on the continental shelf of Southern Vietnam, were monitored in June 2019 when bleaching alert level 1 was announced by NOAA Coral Reef Watch (https:// coralreefwatch.noaa.gov/satellite/index.php) and the surface seawater temperature was recorded between 30-32℃ in the field. We used the ReefCheck transect method (Hodgson et al. 2006) to record cover of bleached corals and non-bleached corals at two depths (shallow: 3-5 m and deep: 6-8 m) at 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…An assessment of a coral bleaching event in the CDNP in June 2019 at five study sites using the ReefCheck protocol revealed high cover of live stony corals (mean 65.6 ± 18%), of which only one-quarter (25 ± 11.1%) were bleached to a different extent [32]. Moreover, out of all the dominant coral taxa in the CDNP, thermally susceptible Acropora and Montipora exhibited only 2.6% and 11% bleached coverage, respectively, whereas thermally resistant massive Porites showed 50% bleached coverage [32,33]. The previous severe thermal anomaly in 2010 was equivalent to that in 2019 (the DHWs of 13 • C-week in 2010 reached NOAA's Second Bleaching Alert Level), and coral bleaching in the CDNP was more pronounced (mean cover of bleached coral was 43.3 ± 21.1%), although the pattern of coral bleaching was similar to that in 2019 with the largest and smallest proportions of bleached corals being Poritidae and Acroporidae, respectively [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An assessment of a coral bleaching event in the CDNP in June 2019 at five study sites using the ReefCheck protocol revealed high cover of live stony corals (mean 65.6 ± 18%), of which only one-quarter (25 ± 11.1%) were bleached to a different extent [32]. Moreover, out of all the dominant coral taxa in the CDNP, thermally susceptible Acropora and Montipora exhibited only 2.6% and 11% bleached coverage, respectively, whereas thermally resistant massive Porites showed 50% bleached coverage [32,33]. The previous severe thermal anomaly in 2010 was equivalent to that in 2019 (the DHWs of 13 • C-week in 2010 reached NOAA's Second Bleaching Alert Level), and coral bleaching in the CDNP was more pronounced (mean cover of bleached coral was 43.3 ± 21.1%), although the pattern of coral bleaching was similar to that in 2019 with the largest and smallest proportions of bleached corals being Poritidae and Acroporidae, respectively [34].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only four publications have highlighted coral bleaching events related to the ENSO in the CDNP in 1998 and 2005 [30,31] and in 2019 during one of the most severe thermal anomalies [32,33]. Results of the coral surveys conducted by CDNP staff yearly at permanent locations using the rapid ReefCheck protocol remain inaccessible to the public.…”
Section: Introductionmentioning
confidence: 99%
“…The bleaching event in Con Dao Island had continued since 1998 (Vo, 2000), to which Acropora is the most susceptible coral genus after 20 years (Vo et al, 2020). In this study, we will analyze the composition of the viral community living in the mucus layer of coral Acropora formosa (Dana, 1846) in healthy and bleached samples by classifying and assigning taxonomy to them went inferring obtained metagenomic sequences from the public database.…”
Section: Introductionmentioning
confidence: 99%